2020
DOI: 10.19044/esj.2020.v16n27p107
|View full text |Cite
|
Sign up to set email alerts
|

Etude Des Plantes Médicinales Utilisées Par Les Femmes Autochtones Pygmées (Batwa) Enceintes Dans L’hinterland Du Parc National De Kahuzi-Biega (Rift albertin, RD. Congo)

Abstract: Introduction: Women become vulnerable to certain pathologies during pregnancy in rural areas and the use of traditional pharmacopoeia using medicinal plants is the solution often adopted. This article focuses on the use of medicinal plants among pregnant indigenous Batwa women living around the Kahuzi Biega National Park (KBNP). The knowledge and practices of these women have enabled us to inventory and determine the different uses of these plants.Methodology: The data used in this study was collected by means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…Other studies have reported various other reasons for using MPs during pregnancy, such as improving the beauty and health of the fetus, and even the intelligence of the future child [ 16 , 20 , 49 , 58 , 59 , 62 , 71 , 72 ], enhancing fetal growth [ 17 , 68 , 73 ], as nutritional supplements, to treat skin problems and urinary tract infections [ 74 ] and to increase milk production during lactation [ 63 ]. It has also been show that MPs can ease pregnancy, improve the course of pregnancy [ 63 ], prevent/treat malaria and prevent miscarriages [ 17 , 40 , 73 , 75 ]. Medicinal plants are also used to fight against sleep disorders, anxiety and fatigue, to control blood sugar and cholesterol levels [ 76 , 77 ], maintain pregnancy, induce labor and facilitate childbirth and delivery, and for postpartum hemostasis [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported various other reasons for using MPs during pregnancy, such as improving the beauty and health of the fetus, and even the intelligence of the future child [ 16 , 20 , 49 , 58 , 59 , 62 , 71 , 72 ], enhancing fetal growth [ 17 , 68 , 73 ], as nutritional supplements, to treat skin problems and urinary tract infections [ 74 ] and to increase milk production during lactation [ 63 ]. It has also been show that MPs can ease pregnancy, improve the course of pregnancy [ 63 ], prevent/treat malaria and prevent miscarriages [ 17 , 40 , 73 , 75 ]. Medicinal plants are also used to fight against sleep disorders, anxiety and fatigue, to control blood sugar and cholesterol levels [ 76 , 77 ], maintain pregnancy, induce labor and facilitate childbirth and delivery, and for postpartum hemostasis [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 14 taxa initially reported by this study as plants with anti-hemorrhoidal uses in Katanga, a literature search revealed that only eight taxa, namely Acmella caulirhiza [135], Aidia micrantha [78], Amaranthus hypochondriacus [136], Anonidium mannii [137], Crossopteryx febrifuga [40,41], Diplorhynchus condylocarpon [37,42,138], Droogmansia munamensis [40], Garcinia punctata [139,140] have previously been documented as medicinal plants in Congolese traditions.…”
Section: Socio-demographic Pro Le Of Persons Consultedmentioning
confidence: 99%
“…Of the 14 taxa initially reported by this study as plants with anti-hemorrhoidal uses in Katanga, a literature search revealed that only eight taxa, namely Acmella caulirhiza [136], Aidia micrantha [79], Amaranthus hypochondriacus [137], Anonidium mannii [138], Crossopteryx febrifuga [40,41], Diplorhynchus condylocarpon [37,42,139], Droogmansia munamensis [40],…”
Section: Socio-demographic Profile Of Persons Consultedmentioning
confidence: 99%